Health Promotion Strategy and Primary Prevention Program at Semmelweis University - Tomcsányi, Teodóra; Csáky-Pallavicini, Roger; Ittzés, Gábor; Semsey, Gábor; Török, Péter (European Journal of Mental Health, 2006)
In contemporary societies, health is widely recognised as the most valuable personal asset. It has undergone significant reconceptualisation in recent decades, of which the Ottawa Charter for Health Promotion (1986) is a major document, advocating empowerment and community mental health thinking. Such concepts have fallen on fertile ground in East Central Europe, where a veritable community mental health promotion movement has sprung up, soon developing institutional means of disseminating the novel views. A discussion of the East Central European scene is introduced by an overview of the emergence and key elements of community mental health thinking and of the possible levels of corresponding intervention. An examination is offered of the deforming effects of dictatorship on community mental health, using the related notions of salutogenesis and Sense of Coherence to deepen the analysis. An exemplary graduate program was developed and established in Hungary even before the Ottawa Charter stated its directive on training. It is designed not so much to convey specialised knowledge as to impart a set of skills and competencies through which helping professionals are better equipped to practice their primary vocation and promote the mental health of the wider community. The program’s goals, contents, structure and specific features are described in detail, emphasising knowledge of self and society, multidisciplinarity, a holistic approach and society building.